PENGARUH TAGLINE DAN BRAND AMBASSADOR TERHADAP PEMBELIAN IMPLUSIF KONSUMEN NEO COFFEE - Izza, Nurrohmatul; Maduwinarti, Ayun; Mulyati, Awin (Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractTagline and Brand Ambbassador is a form of promotion to introduce products to be better known and memorable by consumers. This study aims to find out how much influence Neo Coffee Tagline and Brand Ambassador has on the Purchase of Consumer Impclusive Neo Coffee. In this study the method used is a quantitative approach The method used is to use surve method, by describing the principle on correlational research because it is more focused on explaining the relationship between two or more variables and refining it in an effective way to convey opinions and thoughts. The results of this study show that there is a positive and significant influence of Tagline and Brand Ambassador on the Impulsive Purchase of Neo Coffee consumers. The influence of Tagline and Brand Ambassador on impulsive purchases of 54.1% variable is influential. The remaining 45.9% was influenced by other factors not used in the study. Keywords : Tagline, Brand Ambassador, NEO COFFE, Lucas Wayv.